1986
DOI: 10.1103/physrevb.33.8396
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering and optical-absorption studies of the metastable alloy systemGaAsxSb1

Abstract: The optical properties of GaAs"Sbl "alloys grown across the entire concentration range by multitarget sputter deposition are reported. X-ray diffraction, optical absorption, and Raman spectra show the samples to be single-crystal, single-phase alloys for all x, including those in the miscibility gap. Alloy lattice constants are found to vary linearly with concentration. The direct I -point energy gaps, determined from optical-absorption measurements, show significant negative bowing.Contrary to previous report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 28 publications
3
57
0
Order By: Relevance
“…These values are summarized in table, along with their respective percentages of error for each of the functionals. It was clearly observed that the functionals MBJ and RTPSS showed the lowest percentages of error when being compared to the experimental values reported in the literature [26]. In addition, we note the tendency that the approximations LDA and GGA greatly underestimate the band gap energy of the GaSb compound, as it has been observed in other type III-V semiconductors.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…These values are summarized in table, along with their respective percentages of error for each of the functionals. It was clearly observed that the functionals MBJ and RTPSS showed the lowest percentages of error when being compared to the experimental values reported in the literature [26]. In addition, we note the tendency that the approximations LDA and GGA greatly underestimate the band gap energy of the GaSb compound, as it has been observed in other type III-V semiconductors.…”
Section: Resultssupporting
confidence: 49%
“…The variations found for the prediction of the band-gap energy (E gap ) of the diverse functionals is owed to the approximations that were done in the DFT, at the end of the energy of exchange-correlation, underestimate this value. This is a known error of DFT [26,27] 232.6−237 (ΓLO) [26,27] Table, the values of the structural parameters (a, B 0 ) and the energy of cohesion (E coh ) can be observed, obtained using eight different functionals: LDA, PBE, PBEsol, PW91, rPBE, AM05, TPSS and RTPSS. The reported values are in accordance with the experimental [25] and theoretical [24] data reported by other authors.…”
Section: Resultsmentioning
confidence: 99%
“…org/Nano/24/405707/mmedia). For comparison purposes, we have also plotted the alloy mode dependence found by McGlinn et al on GaAs 1−x Sb x thin films epitaxially grown on GaAs substrates [24]. In this work it was shown that the GaAs 1−x Sb x alloy system exhibits a two-mode behavior.…”
Section: Alloy Phonon Modesmentioning
confidence: 94%
“…This gives impurity mode frequencies of 251 cm −1 and 242 cm −1 for GaSb:As and GaAs:Sb, respectively, fitting relatively well to what has been measured. We have used this estimation for GaAs:Sb, while for GaSb:As we have adjusted it to the experimental value of ∼241 cm −1 [8,24]. On the other hand, following the theory of ionic plasmon coupling as described in [25], the dielectric function of an alloy is expressed as:…”
Section: Alloy Phonon Modesmentioning
confidence: 99%
See 1 more Smart Citation